Strawberry seed extract and its major component, tiliroside, promote ceramide synthesis in the stratum corneum of human epidermal equivalents - Takeda, Shogo; Shimoda, Hiroshi; Takarada, Toru; Imokawa, Genji (PloS one, 2018)
The activation of peroxisomeproliferator-activated receptor (PPAR) α can stimulate the expression of ceramide-related enzymes, and a major component of strawberry seed extract (SSE) tiliroside enhances the expression of PPARα. We determined whether SSE and tiliroside may stimulate ceramide synthesis in the stratum corneum (SC) of the human epidermal equivalents (HEEs) culture model. Treatment with SSE at 1.0 and 3.0 μg/mL elicited a significant increase in the total ceramide content in the SC, which was accompanied by a significant increase in almost all ceramide species except for ceramide [EOS] and [AP]. Treatment with tiliroside at 0.3 μg/mL slightly accentuated the total ceramide content in the SC together with a significant increase in the ceramide [NS, NDS] content. Messenger RNA analysis demonstrated that SSE at 1 or 3 μg/mL significantly stimulated the gene expression of serine palmitoyltransferase (SPT) 2, ceramide synthase (CerS) 3, glucosylceramide synthase (GCS), and β-glucocerebrosidase (GBA) but not of SPT1, sphingomyelin synthase (SMS) 1/2 and acid sphingomyelinase (ASM). In contrast, tiliroside elicited significant increases in the gene expression levels of GCS and GBA only at 0.3 and/or 0.1 μg/mL. Western blotting analysis revealed that both SSE and tiliroside enhanced the protein expression levels of GCS and GBA but not of SPT2 at 1 or 3 and 0.1 or 0.3 μg/mL, respectively. These findings suggested that both SSE and tiliroside have a distinct potential to stimulate the level of ceramide [NS, NDS] in the SC by enhancing the expression of GCS and GBA. The higher stimulatory effect with SSE than tiliroside on SC ceramide synthesis correlates with the significant increase observed with SSE but not tiliroside in the gene expression levels of SPT2 and CerS3. Therefore, it is anticipated that SSE is effective in improving skin barrier function and moisture retention in several ceramide-deficit skin conditions, including surfactant-induced roughened skin, xerosis, and atopic dermatitis.